The use of ex officio to fulfill women's post-divorce rights at the Samarinda Religious Court - Lilik Andar Yuni (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
Problems in fulfilling women's rights after divorce in Religious Courts still exist due to the weakness of supporting elements for the court decisions and their procedures, and obstacles from the ex-couples. Therefore, religious judges are expected to have sensitivity and support for women in making decisions with the value of justice, legal certainty, and benefit. This normative juridical study used statutory and conceptual approaches to explain the use of ex officio in fulfilling iddah and mut'ah living in the Samarinda Religious Court and its suitability to legal purposes. A literary study was done in collecting data by compiling secondary data related to the theme. Then, the data were analyzed using the qualitative descriptive method. Ex officio discourses and legal objectives theory were used to analyze the raised issues. Fulfilling iddah and mut'ah living through ex officio at the Samarinda Religious Court in talaq divorces refers to Supreme Court Regulation (PERMA) No. 3 of 2017, and Circular Letter of Supreme Court (SEMA) No. 1 of 2017. Meanwhile, the application of ex officio in lawsuit divorces refers to PERMA No. 3 of 2017 and SEMA No. 2 of 2019. The fulfillment of women's rights after divorce at the Religious Courts through ex officio aligns with legal objectives: legal certainty, justice, and benefit.